Synchronized B-site alloying for high-efficiency inorganic tin–lead perovskite solar cells - Zhang, Ting; Wang, Feng; Chen, Hao; Qian, Feng; Li, Jian; Zheng, Hualin; Yuan, Shihao; Peng, Xuefeng; Wang, Yafei; Huang, Jiang; Cui, Hao; Yu, Zhinong; et al. (Applied physics reviews, 2023)
Inorganic tin–lead perovskites with low bandgap (1.2–1.4 eV) are desired absorber materials for solar cells owing to their ideal bandgap and compositional stability. However, such tin–lead perovskites are currently subject to inferior power conversion efficiency (PCE) and the origin remains unclear. Here, for the first time, we report the metal-cation-derived unsynchronized crystallization behavior of inorganic tin–lead perovskite, exemplifying by a representative composition CsPb0.7Sn0.3I3. A tin-perovskite-targeted crystallization modulation agent, 1-(4-fluorophenyl) piperazine (1-4FP), is introduced to synchronize the B-site alloying through its strong targeted bonding with SnI2, resulting in substantially enhanced film quality with better morphology and photoelectrical properties. Furthermore, first-principles molecular dynamics simulations reveal that the agent regulates the crystallization route toward the pure phase of CsPb0.7Sn0.3I3 by suppressing the preforming of tin perovskite. With our proposed approach, the best device attains PCE of 17.55%, which is record-high for inorganic tin–lead perovskite solar cells. In addition, treated devices show excellent stability with only 10% and negligible loss after being exposed to 1 sun intensity for 700 h and being stored in N2 after over 4000 h, respectively. Our findings open a new avenue of crystallization route design in inorganic tin–lead perovskites, so as to obtaining high-quality perovskite films and associated solar cells.